Environmental economics and sustainability - Lin, Brian Chi-ang; Zheng, Siqi (Chichester, West Sussex John Wiley and Sons, Inc. Wiley-Blackwell, 2017)
Environmental Economics and Sustainability presents a collection of peer-reviewed research articles contributed by international experts that reveal the current state of our knowledge in the field of environmental economics. -Presents the latest research results on a plethora of issues relating to environmental economics and sustainability -Features original contributions from top experts in the field from around the world -Addresses several of the contemporary challenges of sustainability while infusing new energy into the field of environmental economics -Covers myriad topics relating to environmental economics and sustainability including climate change, air pollution, CO2 emissions, recycling, and the international environmental agreement.
9: GLOBALIZATION AND CLIMATE CHANGE: NEW EMPIRICAL PANEL DATA EVIDENCE; 1. Introduction; 2. Literature Review and Analytical Framework; 3. Empirical Strategy; 4. Empirical Results; 5. Conclusion; Acknowledgements; Notes; References; 10: A SURVEY OF THE LITERATURE ON ENVIRONMENTAL INNOVATION BASED ON MAIN PATH ANALYSIS; 1. Introduction; 2. Knowledge Advances Related to EI; 3. Determinants of EI; 4. Economic Effects of EI; 5. Environmental Effects of EI; 6. Policy Inducement Mechanism; 7. Discussion, Further Developments and Conclusions; Acknowledgements; Notes; References.
"Originally published as a special issue of the Journal of Economic Surveys (Volume 30, Issue 3)" -- tp.
Includes bibliographical references and index.
Keywords: Environmental economics; Sustainable development